PenerapanMetodeContextual Teaching Learning (CTL) dalamMeningkatkanPemahaman Agama PesertaDidik. (StudiKasusPendidikMateriPelajaran Agama di Madrasah Aliyah (MA) Al-Huda SumberNangkaDesaDukoTimur, KecamatanLarangan, KabupatenPamekasan) - Atina, Sitti Mukamilah, Achmad Sya’roni, Abdullah, (AHSANA MEDIA: Jurnal Pemikiran, Pendidikan dan Penelitian Ke-Islaman, 2019)
he period of rapid development of science and technology and the current of globalization which is also more intense has been able to present various problems in the world of education. The diversity of problems in the world of education has quite broad implications. One of them is the low output produced. Madrasah Aliyah Al-Huda is one of the high school institutions under the auspices of the PondokNangka Islamic Boarding School. The purpose of this study is to analyze the factors that influence the students' low understanding of the material taught by religious teachers, describe the professionalism of educators and describe the implications of the method Contextual Teaching Learning (CTL) in improving students' understanding of the material being taught. The researcher analyzed the results of the study using the qualitative method of Miles and Huberman's model through observation, interviews in collecting research data. The results showed that students' contextual teaching learning (CTL) methods were able to receive and digest material well, students were more active during the teaching and learning process as well as increased student learning outcomes which were implied in cognitive, psychomotor and affective mastery.